THE PLACE OF THE SILK NETWORK IN THE NATIONAL ECONOMY AND DEVELOPMENT TENDENCIES (International Congress on Economics, Management and Business Studies, 2026)
Silk production humanity civilization, is one of the ancient industries closely linked to trade routes and cultural exchange processes. It has historically been shaped not only as an economic activity that produced luxurious textile products, but also as an exchange of trade, technology and craftsmanship between peoples. In the current context, the importance of sericulture is not limited to historical heritage; it is an important sector that provides employment in rural areas, increases export earnings, supports local industry and increases the added value of textile products. agro-industry in the direction of is spinning.
Keywords: mulberry plantations, silkworm seed, cocoon cultivation, raw silk production, silk thread and fabric production